A Comprehensive Review on Pyrazole Derivatives as Inhibitors for Iron Protection in Acidic Media: From Molecular Interactions to Corrosion Control - Punitha, N.; Sivakumar, A.; Priya, A. Parvathi; Anitha, M.; Thamizhanban, A. (Asian Journal of Chemistry, 2026)
Corrosion in industrial systems represents a major economic and technical challenge, resulting in annual global losses amounting to several billions of dollars. To mitigate the severe economic and structural impacts of corrosion, researchers are developing efficient and environmentally acceptable inhibitors for metallic materials. Both organic and inorganic inhibitors have been extensively studied for their ability to retard metal degradation in aggressive environments through surface adsorption or passive film formation. Laboratory research had already employed various methods, together with weight loss (WL), potentiodynamic polarisation (PDP) and electrochemical impedance (EIS), to address the issue by 1995. These techniques were implemented through experiments. Atomic force spectroscopy (AFM), scanning electron microscope (SEM) and energy dispersive spectrum (EDX) also utilised as supportive evidence. A focus was placed on organic inhibitors containing heteroatoms as well as extracts/oils from plants. This comprehensive review aims to summarize the recent research status of the compounds containing pyrazole moiety as corrosion protectors for Fe metal in a hydrochloric acid (HCl) environment. There are literature data on corrosion inhibitors that contain these pyrazole derivatives that are used in acid solutions to protect steel. In addition to organic-metal ion complexes, compounds with pyrazole moieties adsorb on metallic surfaces by physical or chemical processes. In general, pyrazole molecules are capable of suppressing both anodic and cathodic corrosion. In the majority of the literature, researchers used the Gaussian 09 program to compare DFT theoretical results with experimental findings.